Surgical treatment of a rare case of hepatocellular carcinoma with right atrial metastasis: A case report. Issue 32 (7th August 2020) - Qiu, Wei; Wang, Chuanlei; Zhang, Ruoyan; Wei, Feng; Shi, Xiaoju; Sun, Xiaodong; Ma, Dashi; Lv, Guoyue; Wang, Guangyi
Abstract: Rationale: Hepatocellular carcinoma (HCC) with intracavitary metastasis extending to the heart, also known as inferior vena cava (IVC) tumor thrombus, is an extremely rare late-stage disease with no effective treatment. In fact, the median survival is reportedly less than 2 months; thus, there is an urgent need for better treatment. Patient concerns: In this study, a 48-year-old patient was admitted to our hospital to seek medical treatment for advanced primary HCC with right atrial metastasis. Diagnosis: The patient was diagnosed as primary HCC with a large mass in the right lobe of the liver and intracavitary metastasis to the right atrium. Interventions: A new surgical treatment of right hemihepatectomy, complete resection of the involved IVC and the right atrium thrombus, plus reconstruction of the resected IVC using autologous pericardial tube graft were undertaken and successfully performed. Outcomes: The patient recovered rapidly, and 14 days after the surgical procedures, he was discharged from the hospital. Notably, serum levels of alpha-fetoprotein dropped to normal range and no clinical signs of recurrence were observed during follow-up. Lessons: This report highlights an unusual case of right atrial metastasis from HCC. The surgical treatment appeared to be suitable and effective, together with postoperative administration of lenvatinib, a tyrosine kinase multitarget inhibitor selected by performing whole-exome sequencing. These therapies have offered favorable clinical outcomes such as prevention of recurrence and prolongation of patient survival. In addition, clinicians may benefit from our experience for their future treatment of patients with similar clinical conditions.